Photoresponsive peptide-azobenzene conjugates that specifically interact with platinum surfaces - Dincer, S.; Tamerler, C.; Sarikaya, M.; Piskin, E. (ELSEVIER, 2008)
The aim of this study is to prepare photoresponsive peptide-azobenzene compounds which interacts with platinum surfaces specifically, in order to create smart surfaces for further novel applications in design of smart biosensors and array platforms. Here, a water-soluble azobenzene molecule, 4-hydroxyazo benzene,4-sulfonic acid was synthesized by diazo coupling reaction. A platinum-specific peptide, originally selected by a phage display technique was chemically synthesized/purchased, and conjugated with the azobenzene compound activated with carbonyldiimidazole. Both azobenzene and its conjugate were characterized (including photoresponsive properties) by FTIR, NMR, and UV-spectrophotometer. The yield of conjugation reaction estimated by ninhydrin assay was about 65%. Peptide incorporation did not restrict the light-sensitivity of azobenzene. Adsorption of both the peptide and its azobenzene conjugate was followed by Quartz Crystal Microbalance (QCM) system. The kinetic evaluations exhibited that both molecules interact platinum surfaces, quite rapidly and strongly. (C) 2008 Published by Elsevier B.V.
Keywords: smart surfaces; platinum-specific peptide; photoresponsive azobenzene conjugates; SELF-ASSEMBLED MONOLAYERS; ADSORPTION-KINETICS; PROTEIN; ORGANIZATION; DESIGN; FILMS; Chemistry; Physics